2018
DOI: 10.1371/journal.pone.0196557
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a simplified in situ protocol on enamel loss after erosive challenge

Abstract: This study investigated the effect of the period of use and location of intraoral appliances on enamel surface loss. This randomized, single blind in situ study was conducted in 2 crossover phases based on the period of use, in which maxillary and mandibular appliances were simultaneously worn. Bovine enamel blocks (n = 120) were randomly divided among the studied groups by surface hardness. In each phase, fifteen volunteers used one maxillary appliance and two mandibular appliances for 5 days. Erosive challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 40 publications
1
5
1
9
Order By: Relevance
“…The night before the beginning of each phase, the volunteers wore the intraoral appliances overnight (11.00 until 7.00) to allow formation of acquired enamel pellicle. Thereafter, volunteers wore the appliance for 5 working days from 7.45 to 18.00 (times could vary +/- 30 min) ( 11 ). The experimental procedure was as follows (all times +/- 15 min): at 7.45 the appliance was worn for pellicle formation; at 8.00 and 10.00 the treatment + erosive challenge was performed; at 12.00 the appliance was removed and stored in wet gauze during lunch; at 13.45 the appliance was worn for pellicle formation; at 14.00 and 16.00 the treatment + erosive challenge; and at 18.00 the appliance was removed and stored in wet gauze during night sleep.…”
Section: Methodsmentioning
confidence: 99%
“…The night before the beginning of each phase, the volunteers wore the intraoral appliances overnight (11.00 until 7.00) to allow formation of acquired enamel pellicle. Thereafter, volunteers wore the appliance for 5 working days from 7.45 to 18.00 (times could vary +/- 30 min) ( 11 ). The experimental procedure was as follows (all times +/- 15 min): at 7.45 the appliance was worn for pellicle formation; at 8.00 and 10.00 the treatment + erosive challenge was performed; at 12.00 the appliance was removed and stored in wet gauze during lunch; at 13.45 the appliance was worn for pellicle formation; at 14.00 and 16.00 the treatment + erosive challenge; and at 18.00 the appliance was removed and stored in wet gauze during night sleep.…”
Section: Methodsmentioning
confidence: 99%
“…Important scientific data regarding preventive measures for erosion comes from in situ models (6,7). The main advantage of the in situ models is the closely resembling of the natural environment due to the presence of salivary flow and acquired pellicle formation (8).…”
Section: Introductionmentioning
confidence: 99%
“…Our research group have been studied different types of in situ appliances with a variety of time use, in order to find a protocol that better simulates a patient at risk of developing dental erosion (6,7,11-13). Santos et al (6) investigated the effect of the period of use and location of intraoral appliances on enamel surface loss and have concluded that the intermittent use of appliances resulted in similar enamel loss compared to the continuous use.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations